Land tenure and farm management efficiency : the case of smallholder rubber production in customary land areas of Sumatra - Suyanto, S.; Tomich, Thomas P.; Otsuka, Keijiro (International Food Policy Research Institute, 1998)
This study attempts to identify the impacts of land tenure institutions on the efficiency of farm management based on a case study of smallholder rubber production in customary lands of Sumatra